(untitled) (Journal of Naval Architecture and Marine Engineering, 2020)
The main objective of this paper is to study the homogeneous-heterogeneous reactions in magnetohydrodynamic flow due to a nonlinear stretching sheet. Analysis for single wall carbon nanotubes with water and pure blood are taken as the base fluids. The governing non-linear partial differential equations are transformed into ordinary which are solved numerically by utilizing the fourth order Runge-Kutta method with shooting technique. Graphical results have been presented for velocity profile, temperature, concentration, local skin friction coefficient and local Nusselt number profiles for various physical parameters of interest. Comparisons with previously published data are performed and the results are found to be excellent agreement.